Perancangan Layanan Print Online Berbasis Website - Muhammad Zulfikar Afifi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In today's modern era, there are still many shops or printing service industries that still carry out marketing through print media such as brochures, banners. And to order it, the customer must come directly to the printing shop, this makes the ordering process less efficient. With the existence of web-based online printing, customers can easily print documents because they don't need to queue at the store, they can be picked up according to their wishes, and the print price has been set by the system. This research was attempted for data collection using interview and observation methods, the system development model used was the waterfall procedure which consisted of 5 stages, namely system requirements analysis, system design, code preparation, system testing and system maintenance. Using the ASP programming language. Net Core and create a database using SQL Server.